2020
DOI: 10.1002/2211-5463.12960
|View full text |Cite
|
Sign up to set email alerts
|

Trifluoperazine induces cellular apoptosis by inhibiting autophagy and targeting NUPR1 in multiple myeloma

Abstract: Multiple myeloma is the second most common hematological malignancy. Trifluoperazine (TFP), an antipsychotic drug, has been reported to exert antitumor effects. Here, our results indicate that TFP targets NUPR1, inhibiting cell growth and inducing apoptosis by autophagy inhibition in multiple myeloma cells. This study provides more directions for the treatment for multiple myeloma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Exposure to TFP or its derivatives was previously reported to result from either induction of autophagy [ 11 , 24 ] or interruption of autophagy flux [ 19 , 25 ], leading to opposite cellular outcomes. To determine whether TFP influences autophagy, PAH-PASMCs were first observed under a bright-field phase-contrast microscope.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to TFP or its derivatives was previously reported to result from either induction of autophagy [ 11 , 24 ] or interruption of autophagy flux [ 19 , 25 ], leading to opposite cellular outcomes. To determine whether TFP influences autophagy, PAH-PASMCs were first observed under a bright-field phase-contrast microscope.…”
Section: Resultsmentioning
confidence: 99%
“…However, in numerous circumstances, autophagy functions as a double-edged sword as both excessive or insufficient levels of autophagic flux can affect cell viability and precipitate cell death [ 32 ]. Although TFP was reported to exert anti-proliferative and anti-survival effects in multiple cancer models [ 12 , 18 , 19 , 25 , 33 ], conflicting data exist regarding the impact of TFP on autophagy and its consequence on cell viability [ 19 , 24 , 34 , 35 ]. Herein, we showed that anti-proliferative and anti-survival effects of TFP were accompanied by induction of autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…25 In most cases, autophagy plays an anti-apoptotic role by raising the stress threshold required for the induction of apoptosis, or by directly suppressing apoptosis. 17,26,27 However, in rare cases, excessive autophagy can lead to ACD of tumour cells due to the extreme degradation of the organelles and cytoplasm. 28,29 In the present study, using RNA-seq, we found that autophagy-related genes were transcriptionally activated by SM in H929 cells (Figure 3C).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, inhibiting autophagy is considered to be a potentially effective strategy against MM 25 . In most cases, autophagy plays an anti‐apoptotic role by raising the stress threshold required for the induction of apoptosis, or by directly suppressing apoptosis 17,26,27 . However, in rare cases, excessive autophagy can lead to ACD of tumour cells due to the extreme degradation of the organelles and cytoplasm 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…The rational of phenothiazine repurposing for cancer therapy has been previously explored and TFP has shown promising anticancer effect in several cancer types ( 42 , 43 , 44 , 45 , 46 ). It was reported to suppress the invasion of metastatic cancer cell lines, by reducing angiogenesis ( 43 ), and to induce lysosome-dependent cancer cell death, through its ability to accumulate in acidic lysosomes (an ability of cationic amphiphilic compounds), thus sensitizing cancer cells to chemotherapy ( 42 , 45 ).…”
Section: Discussionmentioning
confidence: 99%